Special Issue: Applications and Research Trends in Remote Sensing and Geoinformation - Third International Conference on Remote Sensing and Geoinformation of Environment - RSCy2015 - Michaelides, Silas; Themistocleous, Kyriacos; Papadavid, George; Hadjimitsis, Diofantos G. (My University, 2016)
© 2016 S. Michaelides et al. This paper introduces the Third International Conference on Remote Sensing and Geoinformation of Environment - RSCy2015, which was organized by the Cyprus Remote Sensing Society. A brief summary of the institution is made, followed by an overview of selected papers that were presented at this Conference.
Keywords: Cyprus Remote Sensing Society; geoinformation; remote sensing